Kelayakan Ekonomi Agribisnis Ubi Jalar di Desa Sei Beras Sekata Kabupaten Deli Serdang: Economic Feasibility of Sweet Potato Agribusiness in Sei Beras Sekata Village, Deli Serdang Regency - Deras, Stefanus; Maria Tarsisia Luju (Jurnal Agriuma, 2025)
Sweet potato agribusiness has promising economic prospects for both producers and the country. For producers, it serves as a main source of income in rural areas, while for the country, it contributes to foreign exchange earnings due to the high demand in the international market. This study aims to analyze the feasibility of sweet potato farming based on the benefit-cost ratio (B/C) indicator. The research was conducted in Sei Beras Sekata Village, Sunggal District, Deli Serdang Regency. The population consisted of farmers cultivating sweet potatoes on leased land, with a sample size of 31 respondents selected using the census method. The results showed that the B/C ratio was 5.61, meaning that for every IDR 1 spent on farming costs, farmers received a benefit of IDR 4.61 per hectare. The magnitude of the B/C ratio is influenced by the level of income and farming costs. The study found that the income obtained was IDR 59,935,618/ha, while the total costs amounted to IDR 10,696,168/ha. Income was influenced by the quantity and price of production, while costs were affected by the quantity and price of production factors used in sweet potato agribusiness.